Navigating Racialized Belonging: An Asian Critical Race Theory Analysis of Asian International Students’ Experiences in U.S. Counselor Education - John Harrichand (ILIN Education Indonesia, 2026)
Asian international counseling students (ICS) contribute meaningfully to counselor education programs in the United States (US), yet their academic and professional development unfolds within sociopolitical contexts marked by racialization, exclusion, and immigration-related precarity. Guided by Asian Critical Race Theory (AsianCrit), this interpretative phenomenological analysis examined how the current US sociopolitical climate shapes Asian ICS’ adjustment and academic experiences within counselor education. Fourteen current or former Asian ICS enrolled in CACREP-accredited programs participated in semi-structured interviews. Analysis revealed four superordinate themes: Identity, Race, Nationality, and Religion, highlighting experiences of Asianization, perpetual foreigner framing, heightened performance pressures, and challenges to belonging across classroom, advising, supervision, and professional contexts. Participants also described resilience through meaning-making, cultural grounding, and selective support systems. Implications underscore the need for AsianCrit-informed counseling practice, culturally responsive counselor education, and reflexive, equity-oriented supervision that addresses systemic power, transnational stressors, and intersectional identities.